Analysis of Administrative Services at Bumi Ayu Community Health Center UPT, Dumai City - Dewi Jannah; Dila Erlianti; Rudi Hartasetiadi; Reza Syahputra Alfandi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze the quality of administrative services at UPT Puskesmas Bumi Ayu, Dumai City, as part of primary public health service delivery. Service quality is an important indicator of institutional performance and community satisfaction. This research uses a qualitative approach with data collected through interviews, observation, and documentation. Informants consisted of the head of the health center and a service user selected purposively based on direct involvement in administrative services. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The assessment framework applies five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that administrative services generally perform well, particularly in staff responsiveness, procedural reliability, and empathetic interaction. However, several limitations remain, including limited inpatient room facilities and difficulties among elderly users in understanding the Mobile JKN online registration system. These results suggest that service improvement should focus on strengthening physical infrastructure and enhancing user support for digital service access to improve overall administrative service quality in primary healthcare institutions.